Activation of the DNA-binding ability of latent p53 protein by protein kinase C is abolished by protein kinase CK2 - Pospísilová, Sárka; Brázda, Václav; Kucharíková, Katerina; Luciani, M Gloria; Hupp, Ted R; Skládal, Petr; Palecek, Emil; Vojtesek, Borivoj (The Biochemical journal, 2004)
p53 is one of the most important regulators of cell proliferation and differentiation and of programmed cell death, triggering growth arrest and/or apoptosis in response to different cellular stress signals. The sequence-specific DNA-binding function of p53 protein can be activated by several different stimuli that modulate the C-terminal domain of this protein. The predominant mechanism of activation of p53 sequence-specific DNA binding is phosphorylation at specific sites. For example, phosphorylation of p53 by PKC (protein kinase C) occurs in undamaged cells, resulting in masking of the epitope recognized by monoclonal antibody PAb421, and presumably promotes steady-state levels of p53 activity in cycling cells. In contrast, phosphorylation by cdk2 (cyclin-dependent kinase 2)/cyclin A and by the protein kinase CK2 are both enhanced in DNA-damaged cells. We determined whether one mechanism to account for this mutually exclusive phosphorylation may be that each phosphorylation event prevents modification by the other kinase. We used non-radioactive electrophoretic mobility shift assays to show that C-terminal phosphorylation of p53 protein by cdk2/cyclin A on Ser315 or by PKC on Ser378 can efficiently stimulate p53 binding to DNA in vitro, as well as binding of the monoclonal antibody Bp53-10, which recognizes residues 371-380 in the C-terminus of p53. Phosphorylation of p53 by CK2 on Ser392 induces its DNA-binding activity to a much lower extent than phosphorylation by cdk2/cyclin A or PKC. In addition, phosphorylation by CK2 strongly inhibits PKC-induced activation of p53 DNA binding, while the activation of p53 by cdk2/cyclin A is not affected by CK2. The presence of CK2-mediated phosphorylation promotes PKC binding to its docking site within the p53 oligomerization domain, but decreases phosphorylation by PKC, suggesting that competition between CK2 and PKC does not rely on the inhibition of PKC-p53 complex formation. These results indicate the crucial role of p53 C-terminal phosphorylation in the regulation of its DNA-binding activity, but also suggest that antagonistic relationships exist between different stress signalling pathways.
Keywords: nádorový supresorový protein p53; Spodoptera; Protein Structure, Tertiary; Cell Line; kaseinkinasa II; DNA; Phosphorylation; monoklonální protilátky; protein-serin-threoninkinasy; Antibodies, Monoclonal; Tumor Suppressor Protein p53; cyklin-dependentní kinasa 2; Protein Serine-Threonine Kinases; responzivní elementy; vazebná místa; kinasy CDC2-CDC28; zvířata; Humans; proteinkinasa C; Binding Sites; Response Elements; CDC2-CDC28 Kinases; Casein Kinase II; Cyclin-Dependent Kinase 2; buněčné linie; fosforylace; terciární struktura proteinů; Protein Kinase C; lidé; Animals